2015
DOI: 10.4236/jssm.2015.83031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trust and Risk Perception on Citizen’s Intention to Adopt and Use E-Government Services in Jordan

Abstract: This study was undertaken with the primary aim of identifying, examining and providing an understanding of the factors that could affect citizens' intention to adopt and use e-government services in Jordan. The preliminary research model used here had been developed from the Technology Acceptance Model by incorporating additional constructs from other models, namely web trust and perceived risk. A self-administered questionnaire was completed by the selected sample. The response rate was 42.5 percent. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 48 publications
8
19
0
2
Order By: Relevance
“…The result was consistent with the previous studies that also identified Effort Expectancy to have a high impact on technology adoption (Khattab et al, 2015) particularly among local authorities in Malaysia (Pitchay et al, 2016;Zahari, Ariffin, Zamin, & Noor, 2014). Effort Expectancy especially in terms of user friendliness of the service was also found to be significant in both assessing information and conducting transaction with the respective local authority's website.…”
Section: Drivers Of E-government Usesupporting
confidence: 91%
See 3 more Smart Citations
“…The result was consistent with the previous studies that also identified Effort Expectancy to have a high impact on technology adoption (Khattab et al, 2015) particularly among local authorities in Malaysia (Pitchay et al, 2016;Zahari, Ariffin, Zamin, & Noor, 2014). Effort Expectancy especially in terms of user friendliness of the service was also found to be significant in both assessing information and conducting transaction with the respective local authority's website.…”
Section: Drivers Of E-government Usesupporting
confidence: 91%
“…Furthermore, in the context of e-commerce, Perceived Risk was identified to be negatively significant in influencing intention to use of internet banking (Al-Qeisi & Al-Abdallah, 2013). Previous studies (Bélanger & Carter, 2008;Khattab et al, 2015) found that the higher the level of Perceived Risk, the less likely the citizens were to use e-government, and the construct was identified as one of the significant constructs in the context of e-government research (Rana et al, 2013). Similarly, a new Unified Model of E-government Adoption (UMEGA) extended the UTAUT model by adding Perceived Risk as a specific construct .…”
Section: Generating Of Hypothesesmentioning
confidence: 84%
See 2 more Smart Citations
“…What was an application is now just another service composition. And, it's a composition made up of services that very likely participate in other compositions (Al Khattab et al, 2015). Vol.…”
Section: Service-orientation and The Concept Of "Application"mentioning
confidence: 99%